(untitled) (Vietnam Journal of Community Medicine, 2022)
Dyslipidemia is the main cause of atherosclerosis and cardiovascular diseases in patients with type 2 diabetes. Objectives: To investigate the characteristics of lipid components and their relationship with some factors in patients with type 2 diabetes mellitus. Subjects and methods: A cross-sectional descriptive study of 105 patients with type 2 diabetes treated at the Department of Endocrinology and Diabetes, Nghe An General freindship Hospital, from January 2021 - June 2021. Results: The prevalence of dyslipidemia was 86.7%. Individual lipid abnormality of elevated TC, TG, LDL - C and reduced HDL-C were identified in 26.7% , 61.9%, 64.8%, and 47.6% of study subjects, respectively. The prevalence of disorder of 2 lipid components is 25.7%; disorders of 3 lipid components were 23.8% and disorder of 4 lipid componemts were 13.3%. There was a statistically significant positive correlation between waist circumference and TC (r = 0.289; p < 0.05) and TG (r = 0.238; p < 0.05). There is a positive correlation between HbA1c and TC (r = 0.246; p < 0.05), TG (r = 0.297; p < 0.05) and a statistically significant negative correlation between HbA1c and HDL - C (r = - 0.2; p < 0.05). Conclusion: The prevalence of dyslipidemia is found in the majority of patients with type 2 diabetes. Therefore, screening and treatment of dyslipidemia is necessary to prevent cardiovascular complications in diabetic patients.